2008
DOI: 10.1179/106698108790818413
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Anterior-to-Posterior Talocrural Joint Mobilization after Prolonged Ankle Immobilization: A Preliminary Study

Abstract: ABSTRACT:Ankle dorsifl exion range of motion (ROM) typically decreases aft er prolonged immobilization. Anterior-to-posterior talocrural joint mobilizations are purported to increase dorsifl exion ROM and decrease joint stiff ness aft er immobilization. Th e purpose of this study was to determine if a single bout of Grade III anterior-to-posterior talocrural joint mobilizations immediately aff ected measures of dorsifl exion ROM, posterior ankle joint stiff ness, and posterior talar translation in ankles of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 8 publications
3
78
5
1
Order By: Relevance
“…The talus was then glided posteriorly with downward force applied by the mobilising hand (AP) (Houglum, 2010). The joint mobilisation was operationally defined as a grade IV, 1 second rhythmic oscillation with translation taken to tissue resistance (Landrum et al, 2008). The oscillatory technique was chosen in order to load and unload the tissue in a similar way to that which would occur functionally (Banks & Hengeveld, 2010).…”
Section: Joint Mobilisation Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The talus was then glided posteriorly with downward force applied by the mobilising hand (AP) (Houglum, 2010). The joint mobilisation was operationally defined as a grade IV, 1 second rhythmic oscillation with translation taken to tissue resistance (Landrum et al, 2008). The oscillatory technique was chosen in order to load and unload the tissue in a similar way to that which would occur functionally (Banks & Hengeveld, 2010).…”
Section: Joint Mobilisation Interventionmentioning
confidence: 99%
“…Research has also shown that significant increases in DF-ROM can be gained from low dose AP mobilisation treatments. Venturini et al (2007) concluded that a treatment prescription of two, 30 second bouts elicited a 2 0 improvement in DF-ROM, whilst Landrum et al (2008) recorded an increase of 4.4 0 following a single 30 second mobilisation. These studies highlight how minimal treatment doses can produce clinically significant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…11,23,25,43,44,46,[59][60][61][62] Mobilization or manipulation of the talocrural joint has been shown to result in improvements in dorsiflexion ROM and function. 11,13,25,33,38,44,46,59 Specifically, individuals with CAI have been shown to demonstrate increased ankle dorsiflexion ROM and improved balance following talocrural joint mobilization. 33 Because a positional fault of the fibula 35,36 may also contribute to limitations in dorsiflexion ROM following lateral ankle sprains, it is logical that manual interventions directed at the proximal or distal tibiofibular joints may also improve motion and function.…”
Section: T T Conclusionmentioning
confidence: 99%
“…28,29 This might be due to greater available ROM for CF compared to AD. 30 The changes in ROM were comparable to ROM changes recommended as normal response described for other NDTs.…”
Section: Discussionmentioning
confidence: 99%